Mengenal Attention Deficit Hyperactivity Disorder (ADHD) pada anak-anak - Aulya, Ayu Syarifatul (Maliki Interdisciplinary Journal, 2023)
Attention Deficit Hyperactivity Disorder (ADHD), is a disorder during a child’s growth period that can occur from infancy to childhood, due to environmental factors and can continue into adulthood, if not handled properly. ADHD interferes with a child’s focus on something he is facing. Some children with ADHD also experience disturbances in excessive movement or hyperactivity. Children with ADHD will easily be distracted even for things that are not important. ADHD children also have poor memory and self-control. ADHD cannot be simply diagnosed, symptoms in children with ADHD must be observed for some time to diagnose children with indications of ADHD. The role of parents can be a factor and can also be a medicine or treatment for children with indications of ADHD. Labeling that is usually given by teachers and parents to children, without knowing the factors of these actions can worsen the condition of children with ADHD. The behavior patterns of children with ADHD are difficult to distinguish from children of their age, so it is necessary to carry out several psychological tests and observations, so that the symptoms and factors underlying the children with ADHD will be uncovered. Motivation and affection from the people around determine the child’s behavior. Children who are raised with affection tend to behave well, and vice versa, so the role of parents, teachers and the environment is very necessary in handling children with ADHD.